Características da oclusão de crianças participantes do programa de prevenção da saúde bucal - Branco, Adriana Senra de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The purpose of this research was to evaluate the characteristics of occlusion in children that participated in the Oral Health Prevention Program and to compare them with other children in the same age group who did not participate in prevention programs. A total of 100 children between the ages of 5 - 9 years old were examined in the mixed dentition stage (first transitory period and intertransitory period), in the Odontopediatrics Clinic from Faculty of Dentistry of Araçatuba-UNESP. The obtained data were compared with information extracted from literature researches that did not performed dental preventive procedures. The results show that among the 100 patients analyzed, 49% of the children present normal occlusion. On the malocclusions incident 33% present class I, 17% class II, and 1% class III. In addition 3% had anterior crossbites, 5% unilateral posterior crossbites and 1% bilateral posterior bites. Regarding the level of overbite, 84% presents normal overbite with no deep bite, and 17% open bites. When compared with the literature 40.60% presents Class I, 21.60% Class II and 6.20% Class III; 10.41% has anterior crossbites, 6.45% unilateral posterior crossbite, and 2.72% bilateral posterior bite. In relation to the level of overbite, 34.46% present normal overbite, 18.09% deep bite, and 15.85% open bites. The conclusion of this research is that the effective prevention and interception programs should be introduced in the deciduous and mixed teething phase, establishing a more suitable occlusion development

O propósito deste estudo foi avaliar as características oclusais de crianças submetidas ao Programa de Prevenção de Saúde Bucal e comparar com crianças da mesma faixa etária que não participaram de Programas de prevenção. Foram examinadas 100 crianças na faixa de 5 a 9 anos, de ambos os gêneros, no estágio de dentadura mista (1º período transitório e período intertransitório), da Clínica de Odontopediatria da Faculdade de Odontologia de Araçatuba-UNESP. Os dados obtidos, foram comparados com informações extraídas de trabalhos de pesquisa existentes na literatura que não realizaram procedimentos preventivos odontológicos. Os resultados mostram que dentre os 100 pacientes analisados, 49% das crianças apresentaram oclusão normal. Das más oclusões, 33% apresentaram classe I, 17% classe II, e 1% apresentaram classe III. Além disso, 3% apresentaram mordidas cruzadas anterior, 5% mordidas cruzadas posteriores unilateral e 1% mordidas cruzadas posteriores bilateral. Com relação ao nível de sobremordida, 84% apresentaram sobremordida normal, nenhuma mordida profunda, 17% mordidas abertas. Quando comparado com a literatura, 40,60% apresentaram Classe I, 21,60% Classe II e 6,20% apresentaram Classe III; 10,41% apresentaram mordidas cruzadas anterior, 6,45% mordidas cruzadas posteriores unilateral, 2,72% mordidas cruzadas posteriores bilateral. Com relação ao nível de sobremordida, 34,46% apresentaram sobremordida normal, 18,09% mordida profunda, 15,85% mordidas abertas. Conclui-se a necessidade de se introduzir programas eficazes de prevenção e interceptação na fase de dentição ainda decídua e mista, estabelecendo um desenvolvimento mais adequado a oclusão
Keywords: Má oclusão; Oclusão dentária; Epidemiologia; Criança; Saúde bucal; Malocclusion